Development of the KALISAD Application to Improve Structured Sentence Writing Skills among Deaf Students - Suci Rismawati; Endang Pudjiastuti Sartinah; Pamuji Pamuji (Journal La Edusci, 2026)
Children with hearing impairments often experience barriers in accessing language, which affects their mastery of grammar and sentence structure. These limitations make it difficult for deaf students to construct sentences according to Subject, Predicate, Object, and Complement/Adverbial (SPOK) patterns. In addition, conventional learning methods often reduce students’ interest and make it difficult for them to understand sentence structure properly. Therefore, digital learning media are needed to support visual-based learning that suits the characteristics of deaf students. This study aimed to develop the KALISAD application to improve structured sentence writing skills among deaf students and to facilitate a more interactive, attractive, and understandable learning process. This research employed a research and development (R&D) design using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The study used a pretest-posttest approach with quantitative data analysis. The subjects were eight deaf students at the senior high school level of SLB A. Data were collected through observation, interviews, tests, expert validation sheets, and practicality questionnaires. The validation results showed that the KALISAD application was very valid and feasible for use. The instrument validation reached 94.59%, material expert validation 93.18%, media expert validation 94.38%, and deaf education expert validation 96.88%. The practicality score was 88.89%, indicating that the application was practical to use. The effectiveness test using the N-Gain formula showed an average score of 0.42, categorized as moderate. These findings indicate that the KALISAD application is effective, practical, interactive, and appropriate for improving structured sentence writing skills among deaf students.